Extracellular vesicles miR‐210 as a potential biomarker for diagnosis and survival prediction of oral squamous cell carcinoma patients. (1st December 2021) - Bigagli, Elisabetta; Locatello, Luca Giovanni; Di Stadio, Arianna; Maggiore, Giandomenico; Valdarnini, Francesca; Bambi, Franco; Gallo, Oreste; Luceri, Cristina
Abstract: Background: The identification of early diagnostic and prognostic biomarkers in oral squamous cell carcinoma (OSCC) is an unmet clinical need. We hypothesized that extracellular vesicles miR‐210 expression (EV‐miR‐210) could be a potential biomarker for OSCC diagnosis and follow‐up. Methods: The expression of EV‐miR‐210 was measured in the plasma of OSCC patients ( n = 30) and compared to that of controls ( n = 14). Results: The median EV‐miR‐210 expression was significantly higher in OSCC patients compared to controls who had often, undetectable levels ( p < 0.0001). We performed receiver operating characteristic (ROC) analysis for discriminating OSCC cases from controls. EV‐miR‐210 yielded an area under the curve (AUC) of 0.9513 with sensitivity 92.3% and specificity 86.6%. Kaplan‐Meier curves indicated that high EV‐miR‐210 expression was associated with worse 3 years' survival ( p < 0.05). Cox regression hazard model indicated that high EV‐miR‐210, G2, and G3 grading and pathological nodal status (pN)>1 were independent predictors of worse survival in OSCC patients. Conclusion: These preliminary data suggest that EV‐mir‐210 may be a novel diagnostic and prognostic biomarker in OSCC.